Perkembangan Kognitif Anak Usia Dini Usia 5-6 Tahun di TK/Paud Sukacita - Adiani Hulu; Renita Yolanda Sianipar; Loryna Berutu; Christina Pasaribu; Putri Sipahutar; Marisah Simanjuntak (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The purpose of this study is to observe the cognitive development of early childhood in PAUD Sukacita, especially children aged 5-6 years, through learning activities that involve the introduction of body parts and the calculation of numbers. This learning activity is designed to assess children's ability to understand simple concepts, the courage to appear in front of the class, and numeracy skills. The results of the observation showed that the children's responses to the given activities were very different. Some children show good responses, show optimal cognitive development, and show high self-confidence. . However, there are children who have difficulty understanding the material or feel embarrassed when performing in front of their peers. The main causes of this variation are social anxiety, lack of prior stimulation, and differences in confidence levels. These results underscore the importance of methods that support children's emotional and social development and provide appropriate cognitive stimulation to help children maximize their potential.